SOUTH CAUCASUS PALAEOGEOGRAPHY AND PROSPECTIVITY: ELEMENTS OF PETROLEUM SYSTEMS FROM THE BLACK SEA TO THE CASPIAN. (26th June 2021) - Blackbourn, G. A.; Tevzadze, N.; Janiashvili, A.; Enukidze, O.; Alania, V.
Abstract : Nine Mesozoic and Cenozoic palaeogeographic maps are presented to illustrate the petroleum prospectivity of the South Caucasus from a fresh perspective and as part of the wider Caucasus region. Previously, elements of petroleum systems – reservoir, source and sealing lithologies, and the timing of their formation – have mostly been examined within individual sub‐basins or licence blocks, and regional understanding has been limited. Emphasis is placed here on the onshore prospectivity of Georgia and Azerbaijan; the well‐known Pliocene Productive Series of eastern Azerbaijan and the southern Caspian is not considered. The Great Caucasus Basin (GCB) formed in the Early Jurassic following closure of PalaeoTethys, and remained a significant feature, despite structural modifications, until end‐Eocene underthrusting and uplift converted the basin into the Greater Caucasus mountains. By the Toarcian a major delta system had developed along its northeastern margin, while the Transcaucasus block to the south was mostly covered by a shallow sea with limited sediment supply. Bajocian volcanism across the South Caucasus was accompanied by modification of the structure of the Great Caucasus Basin with the intrusion of tholeiitic dykes, possibly associated with onset of northward NeoTethyan subduction. Rising sea levels led to the abandonment of the GCB delta system. Relative uplift of the South Caucasus in the Bathonian created lowlands surrounded by marginal settings in which paralic deposits and coals were laid down. Jurassic hydrocarbon source rocks include deep‐marine shales deposited within the Great Caucasus Basin together with coals; their potential is confirmed by numerous seeps within both Georgia and Azerbaijan. Various Middle Jurassic sandstones are potential reservoirs. Carbonates dominated by the late Callovian, with widespread development of Oxfordian reefs and of Late Jurassic evaporite basins in the North Caucasus. Bedded anhydrites in Georgia comprise potential seals. Shallow‐marine clastics again became widespread across the Caucasus in the Cretaceous, later replaced by carbonates including chalk‐like limestones. Deeper‐marine conditions persisted in the Great Caucasus Basin, which became less well‐defined and split into separate depocentres. Fractured chalks are known reservoirs in the North Caucasus and prospective reservoirs in the South Caucasus. Uplift of the southern South Caucasus during the Paleogene led to northward transport of sediment into evolving E‐W to ESE‐WSW basins in eastern Georgia and western Azerbaijan. Marine deposits within these basins form reservoirs, including thick fractured volcanogenic turbidites in eastern Georgia. Reduced sediment supply here at the start of the Late Eocene allowed organic‐rich restricted‐marine source rocks to accumulate. Rapid uplift of the GCB associated with underthrusting at the end of the Eocene led to emergence of the Greater Caucasus mountains. The prolific Maikopian source rocks were deposited in restricted‐marine conditions during the Oligocene and Early Miocene over the North Caucasus, parts of Azerbaijan and western Georgia, but they are diluted by coarser clastics in eastern Georgia where the Late Eocene source is more significant. Later Miocene uplift of the entire Caucasus region resulted in progressive marine regression, and the formation of potential reservoirs in alluvial and shallow‐marine sands.